Accessibility, acceptability, and effectiveness in primary care of routine telephone review of asthma: pragmatic, randomised controlled trial. Issue 7387 (1st March 2003) - Pinnock, Hilary; Bawden, Robert; Proctor, Stephen; Wolfe, Stephanie; Scullion, Jane; Price, David; Sheikh, Aziz
Abstract: Objective: To determine whether routine review by telephone of patients with asthma improves access and is a good alternative to face to face reviews in general practices. Design: Pragmatic, randomised controlled trial. Setting: Four general practices in England. Participants: 278 adults who had not been reviewed in the previous 11 months. Intervention: Participants were randomised to either telephone review or face to face consultation with the asthma nurse. Main outcome measures: Primary outcome measures were the proportion of participants who were reviewed within three months of randomisation and disease specific quality of life, as measured by the Juniper mini asthma quality of life questionnaire. Secondary outcome measures included the validated "short Q" asthma morbidity score, nursing care satisfaction questionnaire score, and length of consultation. Results: Of 137 people randomised to telephone consultation, 101 (74%) were reviewed, compared with 68 reviewed (48%) of the 141 people in the surgery group, a difference of 26% (95% confidence interval 14% to 37%; P<0.001; number needed to treat 3.8). Three months after randomisation the two groups did not differ in the Juniper score (risk difference −0.07 (95% confidence interval −0.40 to 0.27) or in satisfaction with the consultation (risk difference −0.07 (−0.27 to 0.13)). Telephone consultations were on average 10 minutes shorter than reviews held in the surgery (mean difference 10.7 minutes (12.6 to 8.8; P<0.001)). Conclusions: Compared with face to face consultations in the surgery, telephone consultations enable more people with asthma to be reviewed, without clinical disadvantage or loss of satisfaction. A shorter duration means that telephone consultations are likely to be an efficient option in primary care for routine review of asthma.